PENGUKURAN KESEIMBANGAN LINTASAN PRODUKSI KERAMIK DENGAN METODE HELGESON DAN BIRNIE DI PT.XYZ - Sinaga, Tuti Sarma (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2014)
This research addressed the issue of the PT. XYZ production line balancing which produces powder and ceramic. The completion time of the production line is important because there are differences in the capacity of the machines, especially on powder machine and press machines. This approach is done by using the Helgeson and Birnie method by considering the activities processing time on the production floor. This method increase Balance Delay of powder process at point 0.3333 and Balance Delay of ceramics process in Press A1 and A2 in the Press is 0.1968 and 0.2185. The level of powder process efficiency is 65.82%, while level of powder process efficiency is in Press A1 is 80.31%. The level of efficiency in the production of ceramics in Press A1 is 74.07%